Retinal Morphometric Indicators in Primary Hypothyroidosis and Primary Thyrotoxicosis - V. G. Likhvantseva; V. N. Trubilin; E. V. Korosteleva; S. G. Kapkova; V. A. Vygodin (Oftalʹmologiâ, 2022)
Purpose: to study the morphometric parameters of the retina in patients with primary hypothyroidism and primary thyrotoxicosis by optical coherence tomography.Materials and methods. The material for this study was the results of examination of 54 patients (108 eyes) with thyroid dysfunctions: 32 people (64 eyes) with primary untreated hypothyroidism and 22 people (44 eyes) with primary untreated thyrotoxicosis. To assess the morphometric parameters of the retina, optical coherence tomography was performed.Results. A significant thickening of the layer of nerve fibers was revealed in almost all sectors of the retina of patients with primary hypothyroidism and primary thyrotoxicosis, with the exception of the upper sector in primary thyrotoxicosis. The morphometric parameters of the optic nerve head in both groups were ambiguous. With thyrotoxicosis, the diameter and topographic area of the excavation were less than normal, while the area of the neuroretinal girdle, the area and excavation of the optic nerve head, the ratio of excavation to the area of the optic nerve head, the horizontal and vertical dimensions were higher. In hypothyroidism, the diameter, area and topographic volume of the excavation, the ratio of the excavation to the area of the optic nerve head, the horizontal and vertical dimensions of the excavation to the optic nerve head were below normal, and the length and area of the neuroretinal girdle were higher. In both groups, an increase in the volume and thickness of the retina of all macula’s sectors in combination with a decrease in the minimum thickness of the fovea was revealed. A correlation between the parameters of optical coherence tomography and the rank indicators of the ratio of thyroid hormones was revealed.Conclusion. In primary hypothyroidism and primary thyrotoxicosis, statistically significant morphometric changes in the retina and optic nerve head were revealed. The morphometric data correlated with the rank indices of the thyroid hormone ratios.